2020
DOI: 10.1175/waf-d-20-0001.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impacts of Augmented Observations on the Forecast of Typhoon Wutip’s (2013) Formation Using the Ensemble Kalman Filter

Abstract: Abstract In this study, the impacts of different augmented observations on forecasts of Typhoon Wutip’s (2013) formation are examined. Using the local ensemble transformed Kalman filter (LETKF) implemented for the Weather Research and Forecasting (WRF) Model, it is found that the prediction of Wutip’s formation location and timing is strongly governed by the strength of a monsoon trough that extends from the Bay of Bengal to the Philippine Sea. By properly captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Wutip's formation is strongly rooted in the monsoon trough, as most of the tropical cyclones in the BIEN DONG form within this pattern per year. The performance of WRF-LETKF with augmented observations in this case study has [35].…”
Section: Examplementioning
confidence: 96%
See 2 more Smart Citations
“…Wutip's formation is strongly rooted in the monsoon trough, as most of the tropical cyclones in the BIEN DONG form within this pattern per year. The performance of WRF-LETKF with augmented observations in this case study has [35].…”
Section: Examplementioning
confidence: 96%
“…Ensemble mean distance errors between the forecasted and observed location of Wutip's formation reported at 1200 UTC 25 Sep for three cycles of 48, 36, and 24 h obtained from the WRF-LETKF forecast (black), NDA forecast (stripe), and NAMV forecasts (light shaded) [35].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The initial forecast field using 3DVAR scheme aims at improving the background field for the subsequent assimilation cycles through the stability of the variational assimilation scheme. More details of the assimilation algorithm was described in Tien et al (hereafter, TIEN20) [26].…”
Section: Model Descriptionsmentioning
confidence: 99%
“…Miyoshi and Kunii [21] found that LETKF is particularly useful for handling highly heterogeneous data, such as satellite observations. Multi-physics construction of this scheme within the EPS-DA [26] has demonstrated its effectiveness in forecasting TC Wutip (2013)'s genesis. Motivated from their case study, this study further examines the efficiency of EPS assimilating augmented observations on the forecasts of 45 different TCs from 2012 to 2019.…”
Section: Introductionmentioning
confidence: 99%